Facebook fan page: the effect of perceived socialness in consumer–brand communication. Issue 7 (3rd October 2018) - Hammick, Jinhyon Kwon; Ju, Ilyoung
ABSTRACT: Facebook has become an important platform for a brand–consumer relationship channel. The current study investigates the influence of perceived socialness and its effect on consumers' attitude toward brands. Participants ( N = 404) were recruited in a large southeast university. A 2 (socialness: high vs. low) × 2 (feedback control: high vs. low) × 2 (brand image: high vs. low) between-subject design was conducted. The results of this study identified three important findings. First, high (vs. low) socialness elicited higher perceived relationship commitment, brand trust, and more favorable brand attitude. Second, the effect of socialness on brand attitude was moderated by brand image (positive vs. negative). Third, the mediation analysis showed that the effect of socialness (high vs. low) on brand attitude was fully mediated by perceived relationship commitment and brand trust.